Two Different Translations of Tennyson’s The Idylls of the King into Spanish: The Road From a Text-Oriented Model to a Functional Model of Translation - Zarandona, Juan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis article studies, in some detail, two very different Spanish translations of some of the idylls of Tennyson included in his greatest Arthurian work: The Idylls of the King (XIXth century). The task is approached by means of two different assessment models, Juliane House’s textual one and Christiane Nord’s functional one. The final conclusion will lead to the fact that the assessment of a translation may change dramatically depending on the criteria chosen, as it is here clearly the case.